Analisis Pengaruh Pembiyaan Bmt Arafah Terhadap Pendapatan Umkm. - Atho'ulloh, Rizqi; , Drs. Yuni Prihadi Utomo, MM (2016)
ABSTRACT This study entitled "Analysis Effect of Arafah BMT financing to UMKM in revenue Cemani Ngruki Sukoharjo" the author uses research methods Cross saction. Data used by the author in this study are primary data obtained through direct observation and interviews in the field with a list of questionnaires and secondary data obtained from literartur, books and the Central Bureau of Statistics. From these data dignkan analysis with OLS model. From the results of the analysis using the OLS model, with variable depeden revenue and net income, showed five variables inependen namely Equity, Asset, Workforce, Type of Financing and volume of financing, only the variable capital affect segnifikan on net income customers BMT Arafat, while the dependent variable income no significant effect on revenue. From the results of a second analysis of this dependent variable, test Multicolinearity terdapata no problem Multicolinearity, only variables Assets, Equity, and Labor that there is a problem Multicolinearity. Heteroskidastity test showed no problem heteroscedasticity. Normality Test that ut Normal distribution. From the results of model specifications with mengfunakan Ramsy Reset showed that the linear capital. From the results of the t test variables that have a significant influence on Net Income is variable Initial Capital. While other variables had no significant effect. While on the income variable independent veriabel no significant effect. Based on the analysis revenue R2: 0.829055 (82.91%). Therefore it can be concluded that the five independent variables can explain the effect of variable revenue while the remaining 82.91% 18:09% described other variables. Based on the net profit on the analysis R2: 0.887766 (88.78%) Therefore, it can be concluded that the five independent variables can explain the effect of variable revenue while the remaining 88.78% 12.32% described other variables. Keywords : Revenue, Net Income, Equity, Asset, Employment, Type of Financing, Financing Volume